Application of botulinum toxin in maxillofacial field: part I. Bruxism and square jaw - Kyung-Hwan Kwon; Kyung Su Shin; Sung Hee Yeon; Dae Gun Kwon (SpringerOpen, 2019)
Abstract The application of botulinum in oral and maxillofacial surgery begins in 1982, where Jan Carruthers started using it for reducing the muscle mass and smoothing the skin, and since then it has been used for cosmetic purposes. In Korea, it is already being used by various specialties including dentistry (oral and maxillofacial surgery, oral medicine), plastic surgery, dermatology, ophthalmology, general surgery, and orthopedic surgery, etc. Each specialty approaches to Botox with its own medical indications. In this article, we will discuss the maxillofacial application of botulinum toxin, which includes theoretical and practical aspects of such as bruxism and square jaw.